IMPLEMENTASI STRATEGI DISCOVERY LEARNING DALAM PEMBELAJARAN MATEMATIKA SD - Sukamto . (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2015)
This research is based on the results of integrative thematic learning which has not been optimal yet, for the average score on student learning outcomes has not yet reached the KKM. That is because the new curriculum 2013 which just in progress, the lack of motivation and interest in learning that implied in low student learning outcomes, the lack of media use which is interesting so that the learning activity looks less active, the teacher is still teaching using conventional models, and the models of group investigation have not. Type of ?é?áthis research is classroom action research . The data in this study was obtained through test, observation sheet activities of student and teacher learning activities observation sheet. This study was conducted in three cycles. At each cycle consists of four stages, those are planning, action, observation, and reflection. Based on the analysis result of research data after getting the action,?é?á it has been an increase in student learning outcomes in each cycle, as follows: In the first cycle, student learning outcomes previously only reached 60%, with the value of student activity reached 79%. In the second cycle learning outcomes of students increased to 76%, with the value of student activity reached 85%. In the third cycle of student learning outcomes increased to 92%, with the value of student activity reached 92%. In the third cycle has reached the specified performance indicators, this research is successful.